Morphological characteristic, growth behavior, and cultivation of Luffa acutangula in tropical urban ecosystem: Luffa acutangula in tropical urban ecosystem - Benyamin Lakitan; Fitra Fadhila Rizar; Strayker Ali Muda (Journal of Tropical Life Science, 2022)
Ridge gourd (Luffa acutangula) is a climbing vegetable that produces edible fruits. Young fruits are harvested when the cotyledons have not yet formed. This study covered morphological characteristics, growth behavior, and cultivation practices suitable for increasing the production of the ridge gourd in the urban ecosystem. Results of observation revealed the heart-shape leaf of the ridge gourd was very uniform and the leaf surface was flat so that their leaf area could be accurately estimated using leaf length and/or width (R2 > 0.97), yet leaf thickness was not a reliable predictor for the leaf area (R2 < 0.34). The length of the petioles was not correlated with the leaf blade area. Single leaves, multiple tendrils, bunches of male flowers and/or single female flowers, and one branch could be formed at each stem node. Water content in leaf blade was lower than in the petiole. This phenomenon is related to water favor loss due to transpiration activity. Nevertheless, the total conserved water within the leaf blade was 6.26 times more than that within the petiole. The process of fruit enlargement followed the Sigmoid curve. The upper-end curve flattened 10 days after the female flower bloomed. Moreover, at 10 days, cotyledon has not yet formed. Based on the leaf SPAD value, by time the fruit began to enlarge, 4-5 leaves at the stem base were instigated to show symptoms of senescence. Ridge gourd fruit fresh weight can be best estimated using the length x diameter as the predictor. Â